Principle of Praesumptio iustae Causa or Net Vermoeden van Rechtmatigheid as Principle of Administrative Justice - Muhjad, Muhammad Hadin (Lambung Mangkurat Law Journal, 2016)
One of the principles of administrative justice in procedural law is praesumptio iustae causa (in Latin) or het vermoeden van rechtmatigheid (in Dutch) which is aimed at providing protection to the government in executing the governance from the claim of the citizen(s). However, in Act No. 30 of 2014 it is not well formulated and in the legislation it is not yet applied as a principle in accordance with its function.